2022
DOI: 10.1016/j.breast.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and patterns of breast cancer recurrence in the Malmö Diet and Cancer Study

Abstract: Background: Accumulating evidence suggests that statins have a beneficial effect on breast cancer prognosis. Previous studies have reported a positive association between statin use and breast cancer survival; however, the relationship between statin use and patterns of breast cancer recurrence remains unclear.Patients and methods: We identified all Malm€ o Diet and Cancer Study (MDCS) participants diagnosed with incident invasive breast cancer between 2005 and 2014. The follow-up period began at breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…The knowledge about the risk factors of VTE could be helpful as a piece of prognostic information, but also to eventually target preventive treatment for VTE, since the co-existence of invasive breast cancer and VTE has a significant impact on survival. In particular, new evidence suggests, in humans, a beneficial effect of statins in reducing the risk of breast cancer distant metastasis and in reducing the risk of VTE recurrence [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge about the risk factors of VTE could be helpful as a piece of prognostic information, but also to eventually target preventive treatment for VTE, since the co-existence of invasive breast cancer and VTE has a significant impact on survival. In particular, new evidence suggests, in humans, a beneficial effect of statins in reducing the risk of breast cancer distant metastasis and in reducing the risk of VTE recurrence [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in vitro and in vivo studies have shown that statins inhibit and lower CAV1 levels, hindering its oncogenic role [ 39 , 40 ]. A recent study reported post-diagnostic statin use to protect against distant but not locoregional recurrences [41] , but CAV1’s role in this setting is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility is that cholesterol-lowering may protect against metastases. In the CARE trial ( 7 ), significantly more women in the treatment group suffered from breast cancer, but in a recent study, 360 women with breast cancer were followed for 23 years ( 21 ). After exclusion of those with prediagnostic statin use and those with breast cancer in situ, those who had been prescribed statin treatment during the observation period suffered less often from breast cancer recurrence and lived longer than the untreated.…”
Section: Discussionmentioning
confidence: 99%